2002
DOI: 10.1046/j.1365-2052.2002.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of porcine expressed sequence tags for the construction of a first genomic transcript map of the skeletal muscle in pig

Abstract: To identify genes with effects on meat quality and production traits we developed an adult porcine skeletal muscle cDNA library. After pre-screening this library with seven genes highly expressed in skeletal muscle, 385 non-hybridizing clones were sequenced from both ends to yield 510 expressed sequence tags (ESTs). Together with those ESTs previously generated from this library, we have produced 701 porcine skeletal muscle ESTs. These ESTs were grouped into 306 different cDNA species and compared with the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 41 publications
(65 reference statements)
7
38
0
Order By: Relevance
“…The fragments were cloned and if the PCR product did not exactly match the expected length were sequenced to verify the product (see also additional information, Table 1). Furthermore, 309 sequenced clones of an adult-pig-muscle-specific cDNA library (Davoli et al, 2001) including many muscle structural and energy metabolism-related genes were placed on the microarray. In total the microarray contained 557 genes with known identity and function.…”
Section: Microarray Constructionmentioning
confidence: 99%
“…The fragments were cloned and if the PCR product did not exactly match the expected length were sequenced to verify the product (see also additional information, Table 1). Furthermore, 309 sequenced clones of an adult-pig-muscle-specific cDNA library (Davoli et al, 2001) including many muscle structural and energy metabolism-related genes were placed on the microarray. In total the microarray contained 557 genes with known identity and function.…”
Section: Microarray Constructionmentioning
confidence: 99%
“…Studies have shown that the porcine TTID gene is associated with the SSC2q24-q29 QTL marker (Davoli et al, 2002). The SSC2 region is considered to have some QTLs for average backfat, average daily gain, meat androstenone content, 16-day weight, drip loss, off-flavor, pH, and also other traits (Thomsen et al, 2004;Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TTID plays an indispensable role in stabilizing and anchoring of thin filaments, which may be a prerequisite for correct Z-disc organization (Salmikangas et al, 2003). In porcine, Davoli et al (2002) only mapped the gene to SSC 2q26.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, eight kinds of MyHC isoforms, which are encoded by separate genes, have been found in mammals, and are located on chromosomes 7 and 12 (Weiss et al, 1999;Shrager et al, 2000;Davoli et al, 2002). Only MyHCI, MyHCIIA, and MyHCIIX are expressed in sheep skeletal muscle.…”
Section: Spatial and Temporal Expression Pattern Of Yap1 And Myhcsmentioning
confidence: 99%